Pathogenic PPP2R5D variants disrupt neuronal development and neurite outgrowth in patient-derived neurons that are reversed by allele-specific knockdown - Randee E. Young; Michael V. Zuccaro; Charles A. LeDuc; Noelle D. Germain; Tae Hyun Kim; Patrick Sarmiere; Wendy K. Chung (HGG Advances)
Summary: A significant barrier to the treatment of neurodevelopmental disorders (NDDs) is a limited understanding of disease mechanisms. Heterozygous missense variants in PPP2R5D cause Houge-Janssens syndrome 1, a rare NDD characterized by macrocephaly, developmental delay, intellectual disability, seizures, autism spectrum disorder, and early-onset Parkinson disease. This study investigated the impact of pathogenic PPP2R5D variants on neuronal development and evaluated allele-specific knockdown as a potential therapeutic strategy. Induced pluripotent stem cells derived from individuals carrying the E198K and E420K variants, along with CRISPR-corrected isogenic controls, were differentiated into neural progenitors and cortical glutamatergic neurons. Patient-derived neural progenitors were hyper-proliferative, and glutamatergic neurons differentiated from these cells exhibited increased neurite outgrowth. Notably, neuronal overgrowth phenotypes were not observed in neurons lacking PPP2R5D, suggesting the disorder does not result from loss of function. RNA sequencing (RNA-seq) of glutamatergic neurons derived from patient lines compared to their isogenic controls revealed disruptions in pathways critical for neuronal development, synaptic signaling, and axon guidance. To target pathogenic transcripts, antisense oligonucleotides (ASOs) were designed to selectively knock down the E198K allele, the most common disease-causing missense variant. The most effective ASOs reversed neurite outgrowth defects in patient-derived neurons. These findings uncover molecular mechanisms underlying PPP2R5D-related NDDs and support allele-specific knockdown as a potential therapeutic approach.